Reclaiming American Catholicism: faith, politics, and the future of the Catholic Church - Gehring, John (Georgetown University Press, 2025)
"The Catholic Church in the United States stands at a crossroads between crisis and opportunity. At a time when only the second Catholic President in U.S. history is shaped by the culture and many social justice teachings of his faith, the most vocal leaders in the U.S. Catholic hierarchy embrace a culture-war Catholicism that pits them against President Biden, the pastoral priorities of Pope Francis, and many Catholics in the pews. This book, based on many interviews and the author's own reporting, makes the argument that recalibrating the church's engagement with politics and public life is vital for both the Church and the country. Yet American Catholicism is not simply defined by church politics, theological disputes, or the latest Catholic controversy in the headlines. The Church that Pope Francis envisions - "bruised, hurting and dirty because it has been out on the streets" - can be found every day among Catholic advocates working on the border, in the lives of young Catholics who question the church's teachings but who are active in social justice campaigns, in the persistence of LGBTQ Catholics who carve out tenuous shelters in a church that doesn't accept their full humanity, and in the experiences of seminarians who work in the fields with migrants as part of their religious formation. Throughout, the book incorporates profiles of these Catholics, weaves in on-the-ground reporting, and examines trends that are essential in understanding the Catholic experience in the United States. By illuminating the stories, of these Catholics, the book provides a richer portrait of American Catholicism than most people see in the media, as well as offering living examples of a pastoral and prophetic Catholicism that can serve as inspiration for more systemic reform and renewal"--